2016
DOI: 10.1002/lary.26033
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation via round window or cochleostomy: Effect on hearing in an animal model

Abstract: NA Laryngoscope, 126:E375-E378, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The hearing loss measured in our study spanned several octaves, though conductive hearing loss occurring naturally in humans rarely produces at punctate frequency regions on the audiogram. Others have shown that cochlear implantation can be associated with air-bone gaps (Chole et al 2014; Hod et al 2016; Koka et al 2017) and alterations to immittance measurements (Merchant et al 2020; Scheperle & Hajicek 2019). However, simple attenuation of sound transmission through the middle ear would not be expected to cause the observed shifts in the spatial origins of CAP measurements found in the response area tuning curves of Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…The hearing loss measured in our study spanned several octaves, though conductive hearing loss occurring naturally in humans rarely produces at punctate frequency regions on the audiogram. Others have shown that cochlear implantation can be associated with air-bone gaps (Chole et al 2014; Hod et al 2016; Koka et al 2017) and alterations to immittance measurements (Merchant et al 2020; Scheperle & Hajicek 2019). However, simple attenuation of sound transmission through the middle ear would not be expected to cause the observed shifts in the spatial origins of CAP measurements found in the response area tuning curves of Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…With the observation that ABG may exist after implantation of patients with residual hearing (Chole et al, 2014; Raveh et al, 2014; Mattingly et al, 2016) and in normal-hearing animals after implantation (Hod et al, 2016), this ECochG method can provide an objective tool to estimate reliable ABG without technical issues of measuring behavioral BC thresholds in CI subjects. The fact that this group of subjects had ABG in the presence of normal tympanometry suggests that the ABG originated in the inner ear rather than the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…Rowe et al [19] showed that the RW approach induced delayed low-frequency hearing loss which may be due to the muscle graft used to seal the RW incision. Hod et al [18] showed a similar degree of hearing loss between the RW and cochleostomy approaches in an animal model 1 week after surgery. Above all, few studies have a comprehensive evaluation to indicate the impact of these 2 surgical approaches for CI users using the same type of electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Except for electrode impedance, residual hearing, insertion depth and speech perception were compared between the 2 approaches. The majority of results showed that the 2 approaches provided comparable results for preserving the residual hearing, insertion depth and speech perception [14][15][16][17][18]. Rowe et al [19] showed that the RW approach induced delayed low-frequency hearing loss which may be due to the muscle graft used to seal the RW incision.…”
Section: Introductionmentioning
confidence: 99%